42.0k views
5 votes
Solve the equation. Write a justification for each step. HELP PLEASE!!

−3(−x−2)=5x−9

User TomaszKane
by
6.1k points

2 Answers

1 vote

x =
(15)/(2)

-3( - x - 2 ) 5x - 9 ( distribute parenthesis by multiply terms by - 3 )

3x+ 6 = 5x - 9 ( subtract 5x from both sides )

3x - 5x + 6 = - 9

- 2x + 6 = - 9 ( subtract 6 from both sides )

- 2x = - 15 ( divide both sides by - 2 )

x =
(- 15)/(- 2) =
(15)/(2)


User Isakbob
by
5.1k points
5 votes

x=15/2 distubute the -3

User Hattie
by
6.0k points